Pendataan Penyandang Disabilitas Sebagai Dasar Kebijakan di Kabupaten Sleman Daerah Istimewa Yogyakarta - Nabilla Setya Martha; M. Syafi’ie (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This legal research aims to examine how data collection on persons with disabilities is conducted and how the results are utilized as a basis for policymaking in Sleman Regency. The main focus of the study is on the implementation of the data collection process and its use in policy formulation. The method used is juridical-empirical legal research with policy and sociological approaches. The data consist of primary sources obtained through direct interviews and secondary sources from literature studies, which are analyzed qualitatively. The research subjects include the Sleman Regency Social Service, the Regional Development Planning Agency of Sleman, the Central Bureau of Statistics of Sleman Regency and the Special Region of Yogyakarta, as well as the Association of Persons with Disabilities in Sleman. The results indicate that the implementation of data collection is still not optimal and has not been fully utilized as a policy foundation, as there are still many barriers faced by persons with disabilities in Sleman Regency.